إقليميّة الجديدة والعولمة جدلية العلاقة بين الانتقالية و الانسحاب المصلحي = New regionalism and globalization - Bendebka, Ramzi (Jil Scientific Research Center, 2019)
تحتاج دراسة أيّة ظاهرة في العلاقات الدوليّة إلى رصدها وفهم علاقاتها مع باقي الظواهر المعاصرة لها من خلال ملاحظة التغيّرات الحاصلة أثناء تفاعلها مع بعضها البعض. فمن أبرز سمات وخصائص العلاقات اليوم، وصولها إلى درجة عالية من التعقيد والتداخل الواقع بين مختلف الأجزاء المشكّلة للصورة الكليّة للعالم. ولقد شهد العالم مع نهاية الثمانينات وبداية التسعينات عدّة تغيرات لعل أبرزها بداية التحوّل نحو العولمة مع انهيار القطبية، وإعادة تشكّل الظاهرة الإقليمية كمّاً ونوعاً. إنّ هذا التزامن جعل كلّ ما هو إقليمي متداخل مع مستويين آخرين بقوة، وهما المستوى الدولي والمستوى الداخلي القومي. ومن هنا، سنسعى من خلال هذا العرض إلى ابراز العلاقة الموجودة بين الإقليميّة الجديدة كظاهرة، مع العولمة التي تمثّل الإطار العام للنظام الدولي المعاصر الذي تزامن مع عودة انبعاثها. ففي الوقت الذي يرى فيه بعض العلماء والخبراء في مجال العلاقات الدولية والاقتصاد السياسي أنّ الإقليمية الجديدة هي مرحلة أوّلية وسابقة لبناء العولمة، يرى البعض الآخر بأنّ الإقليمية في الحقيقة تقسّم النظام الدولي إلى قطع منفصلة وإلى كتل متنافسة وبالتالي ماهي إلاّ تراجع وانحراف عن طريق العولمة وليس مرحلة انتقالية سابقة لها (أي العولمة). فهل الإقليمية هي مرحلة سابقة للعولمة أم أنّها انفصال عنها وبالتالي تكون الاقليمية أحد مظاهر تفكّك العولمة؟ ********************************************************************************** The study of any phenomenon in international relations needs to collaborate and understand its relationship with other contemporary phenomena by observing the changes that occur during their interaction with each other. One of the most prominent characteristics of today's relations is its high degree of complexity and interplay between different issues and regions in the world. At the end of the 1980s and the beginning of the 1990s, the world witnessed several changes, most notably the beginning of the globalization transition with the collapse of the polarization and the re-emergence of the regional phenomenon in both quantity and quantity levels. This synchronicity has made every region intertwined with two other levels strongly, namely the international level and the internal national level. Hence, through this study, we will seek to highlight the relationship between the new regionalism as a phenomenon, with globalization, which represents the general framework of the contemporary international order. While some scholars and experts in international relations and political economy believe that the regionalism is an initial and precedent-building stage of globalization, others believe that regionalism in fact, divides the international system into separate pieces and rival blocs. Thus, it is only a decline and a deviation from globalization, and therefore, regionalism is not an earlier stage of transition (ie, globalization).